2022
DOI: 10.1177/03635465221100973
|View full text |Cite
|
Sign up to set email alerts
|

Suture Hook Versus All-Inside Repair for Longitudinal Tears of the Posterior Horn of the Medial Meniscus Concomitant to Anterior Cruciate Ligament Reconstruction: A Matched-Pair Analysis From the SANTI Study Group

Abstract: Background: Secondary meniscectomy rates after repair of longitudinal tears of the posterior horn of the medial meniscus (PHMM) performed concomitantly with anterior cruciate ligament reconstruction (ACLR) are reported to be as high as 25% with an all inside repair technique. Posteromedial portal suture hook repair is an emerging technique; however, it is unknown whether it confers a significantly reduced secondary meniscectomy rate compared with the current gold standard. Purpose/Hypothesis: The primary objec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
27
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(34 citation statements)
references
References 42 publications
1
27
0
Order By: Relevance
“…29,47 Recently, a suture hook repair through a posteromedial portal was found to be associated with a significantly lower secondary meniscectomy rate when compared with the all-inside meniscal repair of longitudinal tears of the posterior horn of the medial meniscus performed at the time of ACLR. 17 These results are similar to the current study and can be compared with the more traditional repair methods that have reported inconsistent results. 6,46 A systematic review in 2017 found no difference in clinical or anatomic failure rates (clinical failure: 11% vs 10%, respectively; anatomic failure: 13% vs 16%, respectively) and similar complication rates of 4.6% for the all-inside technique versus 5.1% for the inside-out technique for isolated meniscal tears.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…29,47 Recently, a suture hook repair through a posteromedial portal was found to be associated with a significantly lower secondary meniscectomy rate when compared with the all-inside meniscal repair of longitudinal tears of the posterior horn of the medial meniscus performed at the time of ACLR. 17 These results are similar to the current study and can be compared with the more traditional repair methods that have reported inconsistent results. 6,46 A systematic review in 2017 found no difference in clinical or anatomic failure rates (clinical failure: 11% vs 10%, respectively; anatomic failure: 13% vs 16%, respectively) and similar complication rates of 4.6% for the all-inside technique versus 5.1% for the inside-out technique for isolated meniscal tears.…”
Section: Discussionsupporting
confidence: 89%
“…1,30,48 Repair of medial meniscal lesions through a posteromedial portal using a suture hook is an emerging technique, with one recent study reporting significantly lower secondary meniscectomy rates when compared with the all-inside meniscal repair, albeit for longitudinal tears of the posterior horn of the medial meniscus with an associated ACLR. 17 The aim of this study was to evaluate the outcomes and failure rates of patients who underwent repair of BHMMTs concomitant with an ACLR using an all-inside repair technique, a suture hook 1 all-inside repair technique, and a suture hook 1 outside-in technique. It was hypothesized that no significant differences in failure rates would be found between the groups at a minimum 2-year follow-up.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…MMRLs can be repaired using inside-out, all-inside, or hybrid combination techniques (outside-in, inside-in, and/or all-inside) 16,17 . While inside-out repairs are more technically challenging, the technique offers greater flexibility with suture placement and the number of sutures placed, potentially creating a stronger repair 12 .…”
Section: Discussionmentioning
confidence: 99%
“…Because reoperation is easiest to identify unequivocally, secondary meniscectomy or subsequent arthroplasty is often used to define failure of meniscal surgery. 7,9,17,23 Symptoms of pain, swelling, catching, or locking may be recorded if patients are interviewed and examined, 1,20 which is often not the case. A meniscal repair that fails to heal or a transplant that extrudes from the joint has probably lost much of its intended function but may not cause symptoms sufficient to warrant an additional procedure.…”
mentioning
confidence: 99%